2007
DOI: 10.1080/10641190701380258
|View full text |Cite
|
Sign up to set email alerts
|

Secondary Compression Features of Jiangsu Soft Marine Clay

Abstract: The results of one-dimensional compression tests conducted on undisturbed specimens of Jiangsu soft marine clay is presented. Because of its high in situ void ratios and natural water content, Jiangsu soft marine clay displays high values of both the virgin compression index, C c , and the secondary compression coefficient, C a . The laboratory data indicates that the value of the ratio C a =C c for Jiangsu soft marine clay is constant. However, neither C a nor C c are constant: they both depend upon the natur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 9 publications
1
2
0
Order By: Relevance
“…[10] found that the ratio of the secondary consolidation coefficient to the compression index is in the range of 0.01 to 0.07 for undisturbed soils and is a constant for the same type of undisturbed soil. is conclusion has been accepted by a number of researchers [11][12][13][14][15]. rough calculation, it was found that the ratios of the secondary consolidation coefficient to the compression index for the Dalian IMTdeposit samples collected from depths of 14, 18, and 25 m ranged from 0.033-0.058, consistent with Mesri's conclusion.…”
Section: Secondary Consolidation Coefficientsupporting
confidence: 77%
“…[10] found that the ratio of the secondary consolidation coefficient to the compression index is in the range of 0.01 to 0.07 for undisturbed soils and is a constant for the same type of undisturbed soil. is conclusion has been accepted by a number of researchers [11][12][13][14][15]. rough calculation, it was found that the ratios of the secondary consolidation coefficient to the compression index for the Dalian IMTdeposit samples collected from depths of 14, 18, and 25 m ranged from 0.033-0.058, consistent with Mesri's conclusion.…”
Section: Secondary Consolidation Coefficientsupporting
confidence: 77%
“…Water content and Atterberg limits (liquid limit and plastic limit) significantly influence secondary compression, which mainly manifests as the effect of water content on deformation [17] and C α [18][19][20]. The main criticism of existing studies is the oversimplification of the compression mechanism, and the different pore water types and their effects are not properly considered.…”
Section: Introductionmentioning
confidence: 99%
“…As a multiphase medium, soft soil's properties are closely related to the soil composition and structural characteristics. Currently, research on the secondary compression deformation law of soil is mainly focused on the influence of pore moisture content, load, loading history and loading time on secondary compression [5][6][7][8][9][10]. There have been some studies on the effects of different soil compositions on the secondary compression characteristics.…”
Section: Introductionmentioning
confidence: 99%